Labeling Consequents of Fuzzy Rules Constructed by Using Heuristic Algorithms of Possibilistic Clustering - Dmitri A. VIATTCHENIN; Stanislau SHYRAI; Aliaksandr DAMARATSKI (Database Systems Journal, 2014)
The paper deals with the problem of automatic labeling output variables in Mamdani-type fuzzy rules generated by using heuristic algorithms of possibilistic clustering. The labeling problem in fuzzy clustering and basic concepts the heuristic approach to possibilistic clustering are considered in brief. Labeling consequents procedure is proposed. Experimental results are presented shortly and some preliminary conclusions are made.